COMPARISON OF FETAL WEIGHT ESTIMATION ACCURACY BASED ON THREE CALCULATION METHODS - Maisarah, Maisarah; Lailiyana, Lailiyana; Yanti, Yanti (Poltekkes Kemenkes Riau Under Health Ministry Republik Indonesia, 2021)
Fetal weight is an indicator of the well-being of fetal growth in the womb and one of the examinations carried out in the initial screening (initial screening) that must be carried out by a midwife when providing antenatal care. The purpose of this study was to determine differences in accuracy of estimated fetal body weight based on Johnson Tausack, Risanto and Dare. This type of research is an analytic survey with a Cross Secsional design with a comparative study approach. This research was conducted in August 2019 until April 2020 in the working area of ​​the Sidomulyo Inpatient Health Center, Pekanbaru City. The number of samples of 30 pregnant women who will give birth were taken using purposive sampling technique. Data collection methods are the measurement of fundal height, abdominal circumference and birth weight of babies with research instruments using fill sheets, tape measures and baby scales. Data analysis used the Kruskal Wallis test at a 95% confidence level. There was no difference in the average difference in birth weight of babies with TBJ between the Johnson Tausack, Risanto, and Dare formulas (p = 0.166).